Synthesis of a new organophosphorous alkoxysilane precursor and its effect on the thermal and fire behavior of a PA66/PA6 copolymer. (May 2015) - Sahyoun, J.; Bounor-Legaré, V.; Ferry, L.; Sonnier, R.; Da Cruz-Boisson, F.; Melis, F.; Bonhommé, A.; Cassagnau, P.
Graphical abstract: Highlights: SiDOPO from vinyl triethoxysilane and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene. Sol–gel of SiDOPO improves fire behavior of polyamide. The SiDOPO filler is created in situ by reactive extrusion. Abstract: A new silicophosphorylated filler was generated in situ in a molten PA66 copolymer during extrusion process with the aim to improve the fire behavior of the matrix. The filler was obtained in one step via hydrolysis–condensation reactions of SiDOPO precursor (DOPO, 9, 10-dihydro-9-oxa-10-phosphaphenanthrene). The synthesis of the precursor is reported and characterized by NMR. A 29 Si NMR study of SiDOPO hydrolysis–condensation reactions in N-methylacetamide (NMA) solvent was also conducted. Thermal stability of Cop-PA/SiDOPO composite and the major degradation products were studied by thermogravimetric analysis coupled with Infrared spectrometry (TGA/FTIR). The Pyrolysis Combustion Flow Calorimeter (PCFC) and cone calorimeter were used to investigate the fire behavior of the composite. Results show that the nanocomposite exhibits a little earlier ignition but with a decrease around 33% of the peak of heat release rate (PHRR). The presence at low concentration of silicon (0.65 wt.%) and phosphorus (0.75 wt.%) promotes the formation of an expanded char layer that acts as a barrier. A reduction of about 18% in effective heat of combustion (EHC) values suggests an additional flame inhibition effect of phosphorus in the gas phase.